HYDATID TORSION OF THE FALLOPIAN TUBE. DIAGNOSTIC DIFFICULTIES (CLINICAL CASE) - Светлана Ивановна Елгина; Дмитрий Евгеньевич Беглов; Вадим Гельевич Мозес; Елена Владимировна Рудаева (The Publishing House Medicine and Enlightenment, 2020)
In the structure of acute gynecological diseases, the torsion of the uterine appendages is 7.0 %. The disease does not always have a typical clinical and laboratory picture, especially in girls, and requires ultrasound research in dynamics. With further increase in size of an organ or the presence adjacent thereto of education, changing echostructure, hemodynamics in the uterus, increasing hydropericardium, the diagnosis of torsion appendages of the uterus will be delivered. The examination will allow timely surgical intervention and will lead to recovery of the patient. The article describes a clinical case of ovarian torsion in a girl of 4 years. Given the above features of the course of the disease, the diagnosis of torsion had difficulties.